Pengaruh Pandemi Covid-19 Terhadap Kecenderungan Stres pada Ibu Hamil di Kalimantan Selatan - Rizki Amalia; Pratiwi Puji Lestari; Zaiyidah Fathony (BULLET : Jurnal Multidisiplin Ilmu, 2022)
− Introduction: The COVID-19 pandemic can threaten the psychological health of pregnant women such as anxiety, stress, and depression. The aims of this study was to determine the effect of the COVID-19 pandemic on the stress tendency of pregnant women. Methods: a cross-sectional study on pregnant women in the province of South Kalimantan. The inclusion criteria in this study were pregnant women who live in South Kalimantan Province; pregnant women in the 1st, 2nd, and 3rd trimesters; pregnant women who are exposed, not exposed, have been exposed, and have never been exposed to COVID-19; pregnant women who have a smartphone device. respondents in this study were 60 respondents. Perceived stress was assessed using the Perceived Stress Scale (PSS) questionnaire, which was distributed through social media Results: The results of the study showed that there were differences in the tendency of stress experienced by pregnant women during a pandemic and not a COVID-19 pandemic (p value 0.005). Analysis of the effect of the variable gestational age (p 0.44) and discomfort during pregnancy (p 0.07) showed that there was no tendency to stress in pregnant women. Conclusions: The gestational age and discomfort experienced by pregnant women do not indicate a tendency to stress in pregnant women. However, the COVID-19 pandemic has a tendency to have a significant effect on the stress of pregnant women. Health workers need to take preventive and curative measures to help pregnant women who experience stress.